Ti-Nb-based alloy material with natural aging strengthening and preparation method of Ti-Nb-based alloy material

By introducing carbon elements into Ti-Nb-based alloys and adjusting niobium content, combined with heat treatment technology, natural aging strengthening is achieved, and the problem of insufficient strength and wear resistance of β-titanium alloys is solved, the process is simplified and the risk of pollution is reduced.

CN119194163APending Publication Date: 2024-12-27HUNAN UNIV
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411613444.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-13
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

The existing beta titanium alloys have shortcomings in strength and wear resistance, and the traditional artificial aging treatment is complex and easy to contaminate, making it difficult to effectively regulate the elongation of TiCx precipitation.

Method used

By introducing an appropriate amount of carbon element into the Ti-Nb-based alloy and adjusting the content of niobium element, appropriate heat treatment is carried out to form a carbon supersaturated solid solution, and the influence of niobium on carbon solubility is used to achieve natural aging strengthening. Specific steps include vacuum smelting, homogenization treatment, hot rolling and solid solution quenching, controlling the diffusion of carbon elements and the precipitation of TiCx.

Benefits of technology

It significantly improves the strength and surface hardness of the material, simplifies the preparation process, reduces environmental pollution and industrial carbon emissions, while taking into account the plasticity and corrosion resistance of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119194163A_ABST
    Figure CN119194163A_ABST
Patent Text Reader

Abstract

The invention discloses a Ti-Nb based alloy material with natural aging strengthening and a preparation method of the Ti-Nb based alloy material. The Ti-Nb-based alloy material comprises the following components in percentage by mass: 16 to 30 percent of Nb, 0.08 to 0.25 percent of C and the balance of Ti; the preparation method comprises the following steps: firstly, carrying out vacuum arc melting on the raw materials to obtain a cast ingot, then carrying out homogenization treatment on the cast ingot to obtain a homogenized blank, then carrying out hot rolling on the homogenized blank to obtain a hot-rolled plate, and finally, carrying out solid solution and quenching treatment on the hot-rolled plate to obtain the Ti-Nb-based alloy material with the natural aging strengthening function. According to the Ti-Nb-based alloy material provided by the invention, the precipitation of TiCx in the alloy is regulated and controlled by utilizing a natural aging phenomenon, the strength of the alloy material is remarkably improved while relatively high plasticity is maintained, and the process is simplified and the industrial carbon emission is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The embodiments of the present invention generally relate to the technical field of titanium alloys, and more particularly to a Ti-Nb-based alloy material with natural aging strengthening and a preparation method thereof. Background Art

[0002] Titanium and titanium alloys are widely used in the field of implantable medical devices due to their high strength, low density, excellent corrosion resistance, and outstanding biocompatibility. The clinical use of the traditional medical titanium alloy material Ti-6Al-4V is greatly limited due to the potential toxicity of its constituent elements V and Al, as well as the "stress shielding" effect caused by the mismatch between its Young's modulus and that of human bone. At present, β-titanium alloys with lower elastic modulus and better biocompatibility, including Ti-Nb-based alloys, have become the main direction of research and development of medical titanium alloys.

[0003] However, the existing β-titanium alloy has the disadvantages of relatively low strength and poor wear resistance, which also limits its clinical use. In the prior art, although titanium carbide TiC can be obtained by introducing interstitial element carbon into β-based titanium alloy, x Precipitate phase, thereby improving the strength and surface hardness of the material, but the brittle TiC x It is not conducive to maintaining the elastic modulus, plasticity and corrosion resistance of the material, and TiC x The precipitation often occurs preferentially at the grain boundaries, which still leads to a decrease in the plasticity of the material and an increase in the elastic modulus.

[0004] Therefore, in order to optimize the mechanical properties of the material, the precipitation behavior of the second phase in the alloy must be controlled. At present, the aging treatment of carbon-containing titanium alloys is mainly medium-temperature artificial aging, and it mainly focuses on the regulation of α phase precipitation. x There is almost no aging control for this major factor affecting elongation. In addition, traditional artificial aging usually requires complex heat treatment processes, which are prone to environmental pollution. Summary of the invention

[0005] In view of the above problems, the present invention provides a Ti-Nb-based alloy material with natural aging strengthening and a preparation method thereof. By utilizing the effect of niobium on the solubility of carbon in the Ti-Nb-based alloy, an appropriate amount of carbon element is introduced and the niobium element content is adjusted, and then a carbon supersaturated solid solution is formed by appropriate heat treatment, and a Ti-Nb-based alloy material with natural aging strengthening can be obtained after cooling.

[0006] To achieve the above object, the present invention discloses a method for preparing a Ti-Nb-based alloy material with natural aging strengthening, comprising the following steps: S1. Placing graphite powder, titanium sponge and niobium particles in a vacuum melting furnace from bottom to top, wherein the graphite powder is wrapped with niobium foil; S2, evacuating the vacuum and filling with protective gas, melting the raw materials to obtain an ingot; S3, performing homogenization treatment on the ingot to obtain a homogenized billet; S4, hot rolling the homogenized billet to obtain a hot-rolled plate; S5. Performing solid solution treatment and quenching treatment on the hot-rolled plate to obtain a Ti-Nb-based alloy material with natural aging strengthening.

[0007] It should be noted that in order to avoid the loss of carbon content due to the splashing of graphite powder during the process of moving, placing and smelting, the present invention wraps the graphite powder with niobium foil.

[0008] Preferably, in the smelting process of step S2, firstly, a current of 140-160A is used to melt the metal components into liquid and wrap the graphite powder, and then a current of 290-310A is used to make the alloy liquid flow to achieve preliminary homogenization of the components. Each ingot is melted 6-8 times, and is turned over after each melting.

[0009] It should be noted that the present invention adopts a smelting method of first using a small current and then a large current in step S2. First, a small current of about 150 A is used to melt the metal components so that the graphite powder is wrapped by the molten metal liquid, and then the current is increased to about 300 A to make the liquid flow to achieve the purpose of preliminary homogenization of the alloy components.

[0010] Preferably, during the homogenization treatment of step S3, the ingot is first heated to 500-600°C in a vacuum sintering furnace at a rate of 8-10°C / min, kept warm for 0.5-1h, then heated to 1000-1300°C at a rate of 3-5°C / min, kept warm for 1-2h, and finally cooled to room temperature with the furnace.

[0011] It should be noted that the present invention adopts graded homogenization treatment in step S3, and effectively controls the temperature and time at the same time, which can prevent the possibility of overburning during high-temperature homogenization and the risk of failure to eliminate segregation during low-temperature homogenization.

[0012] Preferably, during the hot rolling process of step S4, the homogenized billet is first kept at 700-850°C for 0.5-1h and then rolled. The single rolling reduction deformation during rolling is 5%-10%, and the billet is returned to the furnace for 1-3min between passes, with a total deformation of 70%-90%.

[0013] Preferably, in step S4, a titanium alloy anti-oxidation coating is coated on the surface of the homogenized blank before hot rolling.

[0014] It should be noted that the hot rolling operation in step S4 affects the TiC x distribution and morphology, specifically, hot rolling can break up TiC x Particles will also introduce lattice defects in the matrix, which can promote the diffusion and solid solution of carbon atoms in the next solution and quenching process.

[0015] Preferably, during the solution treatment and quenching treatment in step S5, the hot-rolled plate is first vacuum-sealed with a quartz tube, then kept at 1000-1500°C for 1-12 hours, and finally, after the insulation is completed, the quartz tube is broken in water to quickly cool the plate to room temperature.

[0016] It should be noted that the present invention converts the TiC in the Ti-Nb-based alloy into x Dissolve, so that the carbon element is dissolved into the matrix in the form of atoms, thereby forming a carbon supersaturated solid solution after quenching.

[0017] Preferably, the Ti-Nb based alloy material comprises, by mass percentage, Nb 16-30%, C 0.08-0.25%, and Ti as the balance. More preferably, the Ti-Nb based alloy material comprises, by mass percentage, Nb 16-22%, C 0.08-0.2%, and Ti as the balance.

[0018] It should be noted that the natural aging process of carbon-containing titanium alloys is mainly controlled by the diffusion of interstitial carbon atoms. Therefore, the carbon content in the alloy needs to be effectively controlled. If the carbon content is too small, the fine dispersed TiC x Unable to precipitate and unable to obtain natural aging strengthening. If the carbon content is too high, there will be coarse TiC x The presence of affects the plasticity of the alloy.

[0019] Preferably, in step S1, the purity of the graphite powder, titanium sponge and niobium particles is not less than 99.95%, and the thickness of the niobium foil is 0.03-0.05 mm and the purity is not less than 99.95%.

[0020] Preferably, the protective gas in step S2 is argon, which will not react with titanium alloy at high temperature and has very stable chemical properties.

[0021] The invention also discloses a Ti-Nb-based alloy material with natural aging strengthening, and the Ti-Nb-based alloy material is prepared by adopting the above preparation method.

[0022] The technical solution of the present invention has at least the following beneficial effects: The present invention utilizes the characteristic that niobium can sharply reduce the solubility of carbon in the matrix, and cooperates with the heat treatment process to promote the xThe Ti-Nb-based alloy material provided by the present invention has very good natural aging strengthening characteristics, and the natural aging phenomenon can be used to realize the strengthening of TiC in the Ti-Nb-based alloy. x The regulation of precipitation can not only significantly improve the strength of the alloy material while maintaining higher plasticity, but also help simplify the material preparation process and reduce industrial carbon emissions and environmental pollution.

[0023] It should be understood that the contents described in this section are not intended to identify the key or important features of the embodiments of the present invention, nor are they intended to limit the scope of the present invention. Other features of the present invention will become easily understood through the following description. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] The above and other features, advantages and aspects of the embodiments of the present invention will become more apparent with reference to the following detailed description in conjunction with the accompanying drawings. In the accompanying drawings, the same or similar reference numerals represent the same or similar elements.

[0025] Figure 1 1 are SEM images of the Ti-22Nb-0.1C alloy in Example 1 of the present invention, wherein: (a) is when no natural aging is performed; and (b) is when placed at room temperature for 4 months.

[0026] Figure 2 1 and 1 , which are SEM images of the Ti-16Nb-0.2C alloy in Example 2 of the present invention, wherein: (a) is when no natural aging is performed; and (b) is when the alloy is placed at room temperature for 4 months.

[0027] Figure 3 The SEM images of the Ti-22Nb alloy in Comparative Example 1 of the present invention are as follows: (a) is when no natural aging is performed; and (b) is when the alloy is placed at room temperature for 4 months.

[0028] Figure 4 These are SEM images of the Ti-16Nb-0.2C alloy without hot rolling treatment in Comparative Example 2 of the present invention, wherein: (a) is when no natural aging is performed; and (b) is when it is placed at room temperature for 4 months.

[0029] Figure 5 These are SEM images of the Ti-22Nb-0.05C alloy in Comparative Example 3 of the present invention, wherein: (a) is when no natural aging is performed; and (b) is when the alloy is placed at room temperature for 4 months.

[0030] Figure 6 The SEM images of the Ti-22Nb-0.3C alloy in Comparative Example 4 of the present invention, wherein: (a) is when no natural aging is performed; and (b) is when the alloy is placed at room temperature for 4 months. DETAILED DESCRIPTION

[0031] The following is a description of exemplary embodiments of the present invention in conjunction with the accompanying drawings, including various details of the embodiments of the present invention to facilitate understanding, which should be considered as merely exemplary. Therefore, it should be recognized by those of ordinary skill in the art that various changes and modifications may be made to the embodiments described herein without departing from the scope and spirit of the present invention. Similarly, for clarity and conciseness, the description of well-known functions and structures is omitted in the following description.

[0032] Unless otherwise defined, the technical terms used in the following examples have the same meanings as those generally understood by those skilled in the art to which the present invention belongs. Various raw materials, reagents, instruments and equipment used in the following examples can be purchased from the market or prepared by existing methods.

[0033] Example 1: Ti-22Nb-0.1C

[0034] The present embodiment provides a Ti-Nb-based alloy material, and the preparation method is as follows: sponge titanium, niobium particles, graphite powder with a purity of 99.95% and niobium foil with a purity of 99.95% and a thickness of 0.05 mm are used as raw materials, and the raw materials of Nb22%, C 0.1% and Ti 77.9% are weighed according to the mass ratio.

[0035] Graphite powder, titanium sponge and niobium particles are placed in a water-cooled crucible of a vacuum arc melting furnace from bottom to top, wherein the graphite powder is wrapped with niobium foil. After placement, the furnace door is closed and then vacuumed to a vacuum degree of ≤2×10 -3 Pa, filled with argon, and smelted using the tungsten electrode of the melting furnace. During smelting, the melting temperature was controlled by adjusting the current of the vacuum arc melting furnace. First, 150 A was used to melt the top niobium particles, and then the current was increased to 300 A to make the alloy composition initially uniform. After each smelting, the alloy was turned over and smelted repeatedly for 6 times.

[0036] The smelted Ti-22Nb-0.1C alloy ingot was homogenized, and the ingot was heated to 600 °C at a rate of 10 °C / min in a vacuum sintering furnace and kept at that temperature for 0.5 h, then heated to 1000 °C at a rate of 5 °C / min and kept at that temperature for 2 h. After the insulation was completed, it was cooled to room temperature with the furnace.

[0037] The homogenized billet is cut into plates by wire cutting and then hot rolled. The plate is kept at 850 °C for 0.5 h before rolling deformation. The pressing deformation of each pass is 5%. The plate is returned to the furnace for 2 min between passes. The rolling is terminated when the total deformation of the plate reaches 85%. Finally, the hot rolled plate is kept at 1300 °C for 4 h and quickly cooled to room temperature after the insulation.

[0038] The microstructure of the Ti-22Nb-0.1C alloy prepared in this example was examined by SEM. Figure 1 (a), TiC is not observed x The alloy structure is mainly composed of β phase, and a large number of needle-shaped α'' martensite phases can be seen. The mechanical properties of Ti-22Nb-0.1C alloy were further tested, and its yield strength was 1022 MPa, tensile strength was 1175 MPa, and elongation was 10.91%.

[0039] The alloy was placed at room temperature for 1 month, and SEM examination revealed fine dispersed TiC x The yield strength is 1091 MPa and the tensile strength is 1219 MPa, both of which are improved, and the elongation is 10.08%, which is slightly reduced.

[0040] After the alloy was placed at room temperature for 4 months, the SEM test results were shown in Figure 1 (b), fine dispersed TiC x The particle precipitation increased significantly, its yield strength was 1308 MPa, the tensile strength reached 1395 MPa, and the elongation decreased to 8.83%.

[0041] Example 2: Ti-16Nb-0.2C

[0042] The present embodiment provides a Ti-Nb-based alloy material, and the preparation method is as follows: sponge titanium, niobium particles, graphite powder with a purity of 99.95% and niobium foil with a purity of 99.95% and a thickness of 0.03 mm are used as raw materials, and the raw materials of Nb16%, C 0.2% and Ti 83.8% are weighed according to the mass ratio.

[0043] Graphite powder, titanium sponge and niobium particles are placed in a water-cooled crucible of a vacuum arc melting furnace from bottom to top, wherein the graphite powder is wrapped with niobium foil. After placement, the furnace door is closed and then vacuumed to a vacuum degree of ≤2×10 -3 Pa, filled with argon, and smelted using the tungsten electrode of the melting furnace. During smelting, the melting temperature was controlled by adjusting the current of the vacuum arc melting furnace. The top niobium particles were first melted with 140 A, and then the current was increased to 310 A to make the alloy composition initially uniform. The alloy was turned over after each smelting, and the smelting was repeated 8 times.

[0044] The smelted Ti-16Nb-0.2C alloy ingot was homogenized, and the ingot was heated to 500 °C at a rate of 8 °C / min in a vacuum sintering furnace and kept at that temperature for 1 h, and then heated to 1300 °C at a rate of 3 °C / min and kept at that temperature for 1 h. After the holding period, the ingot was cooled to room temperature with the furnace.

[0045] The homogenized billet was cut into plates by wire cutting and then hot rolled. The plates were kept at 700 °C for 1 h before rolling deformation. The pressing deformation of each pass was 8%. The plates were returned to the furnace for 3 min between passes. The rolling was terminated when the total deformation of the plates reached 80%. Finally, the hot rolled plates were kept at 1500 °C for 1.5 h and quickly cooled to room temperature after the insulation.

[0046] The microstructure of the Ti-16Nb-0.2C alloy prepared in this example was examined by SEM. Figure 2 (a), TiC is not observed x The alloy structure is mainly composed of β phase, and a large number of needle-shaped α'' martensite phases can be seen. The mechanical properties of Ti-16Nb-0.2C alloy were further tested, and its yield strength was 873 MPa, tensile strength was 996 MPa, and elongation was 12.66%.

[0047] The alloy was placed at room temperature for 1 month, and SEM examination revealed fine dispersed TiC x The yield strength is 958 MPa and the tensile strength is 1027 MPa, both of which are improved, and the elongation is 11.15%, which is slightly reduced.

[0048] After the alloy was placed at room temperature for 4 months, the SEM test results were shown in Figure 2 (b), fine dispersed TiC x The particle precipitation increased significantly, its yield strength was 1094 MPa, the tensile strength reached 1193 MPa, and the elongation decreased to 9.86%.

[0049] It can be seen from the test results of the above two embodiments that after the Ti-Nb-based alloy prepared by the method of the present invention is placed at room temperature for a period of time, the strength is greatly improved without seriously reducing the elongation of the alloy, thus showing a good natural aging strengthening effect, and within 4 months, as the aging time increases, this strengthening effect becomes more obvious.

[0050] Comparative Example 1: Ti-22Nb

[0051] This comparative example provides a Ti-Nb based alloy material, in which the raw material does not contain the C element, the Nb content is the same as that in Example 1, and Ti is the balance. Other preparation steps are consistent with those in Example 1.

[0052] The microstructure of the Ti-22Nb alloy prepared in this comparative example was examined by SEM. Figure 3 (a), the alloy structure is mainly β phase, and TiC is not observed because no carbon element is introduced. xThe mechanical properties of Ti-22Nb alloy were further tested, and the yield strength was 782 MPa, the tensile strength was 854 MPa, and the elongation was 16.59%.

[0053] The alloy was placed at room temperature for 1 month, and SEM examination showed that no fine dispersed TiC was found. x The yield strength is 801 MPa, the tensile strength is 869 MPa, and the elongation is 16.44%.

[0054] After the alloy was placed at room temperature for 4 months, SEM examination showed that no fine dispersed TiC was found. x Precipitation, test results see Figure 3 (b), its yield strength is 817 MPa, the tensile strength reaches 872 MPa, and the elongation is reduced to 16.18%.

[0055] It can be seen from the test results that after the alloy of this comparative example is placed at room temperature for a period of time, its strength and elongation have no obvious changes, and therefore no significant natural aging strengthening effect is shown.

[0056] Comparative Example 2: Ti-16Nb-0.2C (without hot rolling treatment)

[0057] This comparative example provides a Ti-Nb-based alloy material, whose raw material composition and other preparation steps are consistent with those of Example 2, except that no hot rolling treatment is performed after the homogenization treatment.

[0058] The microstructure of the Ti-16Nb-0.2C alloy prepared in this comparative example was examined by SEM. Figure 4 (a), the alloy structure is mainly β phase, and coarse TiC x The mechanical properties of the Ti-16Nb-0.2C alloy were further tested, and the yield strength was 891 MPa, the tensile strength was 965 MPa, and the elongation was 2.53%.

[0059] The alloy was placed at room temperature for 1 month, and SEM examination showed that only coarse TiC x Granular, no fine dispersed TiC x The yield strength is 905 MPa, the tensile strength is 976 MPa, and the elongation is 2.27%.

[0060] After the alloy was placed at room temperature for 4 months, SEM examination showed that there were still only coarse TiC x Granular, no fine dispersed TiC x Precipitation, test results see Figure 4(b), its yield strength is 927 MPa, the tensile strength reaches 991 MPa, and the elongation is reduced to 2.02%.

[0061] It can be seen from the test results that after the alloy of this comparative example is placed at room temperature for a period of time, its strength and elongation have no obvious changes, so it does not show a significant natural aging strengthening effect, and due to the lack of hot rolling treatment, there are coarse TiC x The particles have low elongation, which affects the plasticity of the material and is not conducive to the production and application of the Ti-Nb based alloy.

[0062] Comparative Example 3: Ti-22Nb-0.05C

[0063] This comparative example provides a Ti-Nb-based alloy material, in which the C content is reduced to 0.05%, the Nb content is the same as that in Example 1, Ti is the balance, and the other preparation steps are consistent with those in Example 1.

[0064] The microstructure of the Ti-22Nb-0.05C alloy prepared in this comparative example was examined by SEM. Figure 5 (a), TiC is not observed x The alloy structure is mainly composed of β phase, and a large number of needle-shaped α'' martensite phases can be seen. The mechanical properties of Ti-22Nb-0.05C alloy were further tested, and its yield strength was 926 MPa, tensile strength was 969 MPa, and elongation was 12.17%.

[0065] The alloy was placed at room temperature for 1 month, and SEM examination showed that no fine dispersed TiC was found. x The yield strength is 944 MPa, the tensile strength is 972 MPa, and the elongation is 12.01%.

[0066] After the alloy was placed at room temperature for 4 months, SEM examination showed that no fine dispersed TiC was found. x Precipitation, test results see Figure 5 (b), its yield strength is 961 MPa, the tensile strength reaches 998 MPa, and the elongation is reduced to 11.89%.

[0067] It can be seen from the test results that after the alloy of this comparative example is placed at room temperature for a period of time, its strength and elongation have no obvious changes, and therefore no significant natural aging strengthening effect is shown.

[0068] Comparative Example 4: Ti-22Nb-0.3C

[0069] This comparative example provides a Ti-Nb-based alloy material, in which the C content is increased to 0.3%, the Nb content is the same as that in Example 1, Ti is the balance, and the other preparation steps are consistent with those in Example 1.

[0070] The microstructure of the Ti-22Nb-0.3C alloy prepared in this comparative example was examined by SEM. Figure 6 (a), the alloy structure is mainly β phase, and a large number of needle-shaped α'' martensite phases can be seen. Although the solution temperature is as high as 1500℃, coarse TiC x The mechanical properties of Ti-22Nb-0.3C alloy were further tested, and the yield strength was 1196 MPa, the tensile strength was 1271 MPa, and the elongation was 2.04%.

[0071] The alloy was placed at room temperature for 1 month, and SEM examination showed coarse TiC x The particles still exist, and small dispersed TiC is also found. x The particles precipitated, and their yield strength was 1248 MPa and tensile strength was 1336 MPa, both of which were improved, but the elongation was only 1.79%.

[0072] After the alloy was placed at room temperature for 4 months, SEM examination showed coarse TiC x The particles still exist, and the fine dispersed TiC x The particle precipitation increased significantly. For the test results, see Figure 6 (b) The results show that its yield strength is 1385 MPa, the tensile strength reaches 1422 MPa, and the elongation is as low as 1.53%.

[0073] From the test results, it can be seen that the strength of the alloy of this comparative example is greatly improved after being placed at room temperature for a period of time, but due to the excessive carbon content, there are coarse TiC x The particles result in low elongation, which affects the plasticity of the material and is not conducive to the production and application of the Ti-Nb based alloy.

[0074] The embodiments of the present invention have been described above, and the above description is exemplary, not exhaustive, and is not limited to the disclosed embodiments. Many modifications and variations will be apparent to those of ordinary skill in the art without departing from the scope and spirit of the described embodiments. The selection of terms used herein is intended to best explain the principles of the embodiments, practical applications, or technical improvements in the market, or to enable other persons of ordinary skill in the art to understand the embodiments disclosed herein.

Claims

1. A method for preparing a Ti-Nb-based alloy material with natural aging strengthening, characterized in that: The steps include: S1. Placing graphite powder, titanium sponge and niobium particles in a vacuum melting furnace from bottom to top, wherein the graphite powder is wrapped with niobium foil; S2, evacuating the vacuum and filling with protective gas, melting the raw materials to obtain an ingot; S3, performing homogenization treatment on the ingot to obtain a homogenized billet; S4, hot rolling the homogenized billet to obtain a hot-rolled plate; S5. Performing solid solution treatment and quenching treatment on the hot-rolled plate to obtain a Ti-Nb-based alloy material with natural aging strengthening.

2. The method for preparing a Ti-Nb-based alloy material having natural aging strengthening according to claim 1, characterized in that: In the smelting process of step S2, firstly, a current of 140-160A is used to melt the metal components into liquid and wrap the graphite powder, and then a current of 290-310A is used to make the alloy liquid flow to achieve preliminary homogenization of the components. Each ingot is smelted 6-8 times, and turned over after each smelting.

3. The method for preparing a Ti-Nb-based alloy material with natural aging strengthening according to claim 1, characterized in that: During the homogenization treatment process of step S3, the ingot is first heated to 500-600°C at a rate of 8-10°C / min in a vacuum sintering furnace, kept warm for 0.5-1h, then heated to 1000-1300°C at a rate of 3-5°C / min, kept warm for 1-2h, and finally cooled to room temperature with the furnace.

4. The method for preparing a Ti-Nb-based alloy material with natural aging strengthening according to claim 1, characterized in that: During the hot rolling process of step S4, the homogenized billet is first kept at 700-850°C for 0.5-1h, and then rolled. The single rolling deformation during rolling is 5%-10%, and the billet is returned to the furnace for 1-3min between passes, with a total deformation of 70%-90%.

5. The method for preparing a Ti-Nb-based alloy material with natural aging strengthening according to claim 1, characterized in that: During the solution treatment and quenching treatment in step S5, the hot-rolled plate is first sealed with a quartz tube in vacuum, then kept at 1000-1500° C. for 1-12 hours, and finally, after the insulation is completed, the quartz tube is broken in water to quickly cool the plate to room temperature.

6. The method for preparing a Ti-Nb based alloy material with natural aging strengthening according to any one of claims 1 to 5, characterized in that: The Ti-Nb based alloy material comprises, by mass percentage, 16-30% Nb, 0.08-0.25% C and the balance Ti.

7. The method for preparing a Ti-Nb-based alloy material with natural aging strengthening according to claim 6, characterized in that: The Ti-Nb based alloy material comprises, by mass percentage, 16-22% Nb, 0.08-0.2% C and the balance Ti.

8. The method for preparing a Ti-Nb based alloy material with natural aging strengthening according to claim 7, characterized in that: In the step S1, the purity of the graphite powder, titanium sponge and niobium particles is not less than 99.95%, and the thickness of the niobium foil is 0.03-0.05 mm and the purity is not less than 99.95%.

9. A Ti-Nb based alloy material with natural aging strengthening, prepared by the preparation method according to any one of claims 1 to 8.

Citation Information

Cited By

  • Microstructure and performance optimized TiNiCuNb alloy and preparation method thereof

    CN120193181A